DETERMINANTS OF BALANCE OF PAYMENTS IN KENYA - Kennedy, Osoro (European Scientific Journal, ESJ, 2013)
This study investigates the long-run determinants of balance of payment dynamics in Kenya between 1963 and 2012, using co integration and error correction mechanism. The study uses annual time series data for Kenya. The paper examines how the determinants of balance of payments lead to adjustments in removing disequilibrium in the balance of payments position. Results show that variables, which exhibited non-stationarity, were insignificant in determining the balance of payments in the long run. However, the results of the variables identified ,confirmed that balance of payments co integrated, suggesting that balance of payments fluctuations could be caused by the level of trade balance, exchange rate movement and foreign direct investment inflow. The investigation further reveals that FDI and Exchange rates are the main determinants of balance of payments. The positive effect of FDI leads to the development of new products and services which eventually causes an improvement in the balance of payments via expansion of exports. Thus, the findings of this study show that balance of payments is both a monetary and real phenomenon.